Mirror Image Modeling of Acetabular Rim Thickness Differences in Patients With Unilateral Femoroacetabular Impingement Syndrome - Andrew J. Riff, M.D; Alexander E. Weber, M.D; Timothy C. Keating, M.D; Benedict U. Nwachukwu, M.D., M.B.A; Edward C. Beck, M.D., M.P.H; Nozomu Inoue, M.D., Ph.D; Laura M. Krivicich, B.S; Shane J. Nho, M.D., M.S (Elsevier, 2019)
Purpose: To use mirror imaging to identify the location and magnitude of difference in acetabular rim morphology between the symptomatic and unaffected acetabula in patients with symptomatic unilateral pincer-type or mixed femoroacetabular impingement syndrome (FAIS) using 1-dimensional models created with computed tomography (CT). Methods: CT scans of bilateral hips in 33 patients diagnosed with unilateral pincer-type or mixed FAIS were obtained. Three-dimensional bilateral hip models were constructed, and the unaffected hemipelvis was superimposed onto the symptomatic side to compare acetabular thickness. Protrusion of the symptomatic side was recorded, and rim morphology was divided into clock face quadrants to analyze the location of greatest magnitude of difference between affected and unaffected acetabula. Analysis of the quadrants was performed using analysis of variance with post hoc Bonferroni correction. Results: The study group consisted of more females (51.6%) than males, with an average age of 35.72 ± 7.8 years and an average body mass index of 24.3 ± 4.1 kg/m2. Of the 33 hips included, 14 were isolated pincer-type FAIS and 19 were mixed. The average preoperative symptomatic side lateral center edge angle was 37.5° ± 7.2° compared with 29° ± 5.1° on the asymptomatic side (P = .001). The symptomatic acetabular rim was on average 0.43 ± 0.18 mm thicker than the corresponding location on the unaffected rim. When the acetabulum was divided into clock face quadrants, the 12 to 3 o'clock position showed the greatest difference between symptomatic and unaffected sides (0.55 ± 0.18 mm) compared with the 3 to 6 o'clock position (0.4 ± 0.28 mm; P = .006), 6 to 9 o'clock (0.34 ± 0.07 mm; P < .001), and 9 to 12 o'clock (0.38 ± 0.03; P = .001). Conclusions: Patients with unilateral, symptomatic pincer-type or mixed FAIS show statistical differences in rim thickness between the affected and unaffected acetabula. Small changes in acetabular rim morphology on the order of ≤0.5 mm may be the difference between symptomatic FAIS and the unaffected hip. Level of Evidence: IV, case series.